DATA MINING Techniques for Fundraisers: Explaining the Portuguese Donors Behavior - Laureano, Raul M. S.; Abreu, M. E. (ARNOVA 14, 2014)
This paper predicts the relationships of donation practices drivers with other variables like altruism, prosocial behavior and religious constructs, via a classification and regression tree. The study predicts that religiosity and religious affiliation are the most important attributes for donation practices. Implications for the findings and potential use for fundraisers are also discussed. Fundraising managers in nonprofit sector are constantly challenged to obtain donations from the general population. Rather than simply requesting donors to donate, it has become a far and wide practice to suggest a set of amounts – the appeals scale. We study the relationship between what is requested and what is received by incorporating donor psychological profile into a comprehensive, ‘attraction’-based model of donation behavior. Using data collected from 612 Portuguese individual charities donors, we compare several data mining algorithms to explain donation behavior. The models evidence good quality and the extracted knowledge is useful for fundraisers and marketing campaigns allowing a higher efficiency.